2018
DOI: 10.1002/int.22066
|View full text |Cite
|
Sign up to set email alerts
|

A new divergence measure for basic probability assignment and its applications in extremely uncertain environments

Abstract: Information fusion under extremely uncertain environments is an important issue in pattern classification and decision‐making problems. The Dempster‐Shafer evidence theory (D‐S theory) is more and more extensively applied in dealing with uncertain information. However, the results contrary to common sense are often obtained when combining different evidence using Dempster's combination rule. How to measure the difference between different evidence is still an open issue. In this paper, a new divergence is prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
62
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 96 publications
(62 citation statements)
references
References 50 publications
(57 reference statements)
0
62
0
Order By: Relevance
“…Fuzzy logic was developed by Zadeh and Mamdani and Assilian, based on which the concept of approximate reasoning was introduced and showed that vague logical statements enable the formation of algorithms that can use vague data to derive vague inferences. Many theories have been promoted by this method, such as Dempster‐Shafer theory, Z‐numbers, and fuzzy reasoning . The definition of fuzzy sets is given as follows:…”
Section: Fuzzy Sets and Ivfssmentioning
confidence: 99%
“…Fuzzy logic was developed by Zadeh and Mamdani and Assilian, based on which the concept of approximate reasoning was introduced and showed that vague logical statements enable the formation of algorithms that can use vague data to derive vague inferences. Many theories have been promoted by this method, such as Dempster‐Shafer theory, Z‐numbers, and fuzzy reasoning . The definition of fuzzy sets is given as follows:…”
Section: Fuzzy Sets and Ivfssmentioning
confidence: 99%
“…We can come to the conclusion that PFS can represent more uncertainty than IFS, consequently, PFS is more useful than IFS in MCDM issues. Furthermore, PFS has been extensively investigated from multiple perspectives, such as aggregation operators, decision methods and other applications …”
Section: Introductionmentioning
confidence: 99%
“…The intuitionistic fuzzy sets (IFSs) proposed by Atanassov can be seen as the generalization of the fuzzy sets presented by Zadeh, which can be denoted as an intuitionistic fuzzy number (IFN) for a single element. IFSs can represent more information than fuzzy sets by including membership and nonmembership degrees in its framework, which extends its applications in many fields, such as pattern recognition, especially multicriteria decision‐making (MCDM) problems …”
Section: Introductionmentioning
confidence: 99%